Optical glass, prefabricated member thereof, optical element and optical instrument
By reasonably selecting and proportioning the components of optical glass and optimizing their composition, the problems of poor thermal expansion coefficient and wear performance of existing optical glass are solved, and the effects of low thermal expansion coefficient and excellent wear are achieved.
Patent Information
- Application Number
- CN202411351095.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2025-02-25
AI Technical Summary
The thermal expansion coefficient and wear performance of existing optical glasses are poor, resulting in easy cracking during processing, reducing yield and limiting its application.
By reasonably selecting and proportioning SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5, Gd2O3, ZnO, Ta2O5 and other components, control the (Gd2O3+ZnO)/Y2O3 ratio below 2.0, optimize the composition of the glass, reduce the thermal expansion coefficient and increase the wear level.
The low thermal expansion coefficient and excellent wear degree of optical glass are achieved, and the processing performance and application range of glass are improved.
Smart Images

Figure BDA0005062382620000121 
Figure BDA0005062382620000131 
Figure BDA0005062382620000151
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical glass, and in particular to an optical glass, a preform thereof, an optical element and an optical instrument. Background Art
[0002] In recent years, various optical instruments such as digital cameras, camcorders, projectors and projection TVs have been developing towards miniaturization and lightness. In order to achieve miniaturization and lightness of optical instruments, it is necessary to reduce the number of lenses and prisms used in the optical system. Optical glass with a refractive index of 1.82 to 1.89 and an Abbe number of 37 to 44 belongs to high-refractive-index optical glass. High-refractive-index optical glass can obtain a larger viewing angle with a smaller volume, thereby reducing the number of optical glasses used in optical instruments, so its demand is very widespread.
[0003] In the prior art, glass preforms can be made by mechanical processing such as grinding and lapping of optical glass, or by making a preform for molding from optical glass, hot pressing the preform and then grinding the preform to make a glass preform, or by precision stamping the preform made by grinding to make a glass preform. This requires that the optical glass has good processing performance and excellent abrasiveness. On the other hand, due to its large thermal expansion coefficient, optical glass is prone to breakage during processing, which reduces the yield rate of the glass; at the same time, the large thermal expansion coefficient will cause the glass to have poor thermal shock resistance, thereby limiting the application of optical glass. Therefore, there is an urgent need for an optical glass with a low thermal expansion coefficient and excellent abrasiveness.
[0004] This application is a divisional application for the invention patent application with application number 202211031611.3, application date August 26, 2022, and name “Optical Glass”. Summary of the invention
[0005] The main purpose of the present application is to provide an optical glass, its preform, optical element and optical instrument, aiming to solve the technical problems of poor thermal expansion coefficient and abrasion performance of existing optical glass.
[0006] To achieve the above object, the present application proposes an optical glass, which comprises the following components by weight percentage:
[0007] SiO2: 2-15.2%; B2O3: 8-22%; La2O3: 40-60%; Y2O3: 3-18%; ZrO2: 1-15%; Nb2O5: 2-15%; Gd2O3: 0-9%; ZnO: 0-10%; Ta2O5: 0-10%; TiO2: 0-6%; RO: 0-10%; Rn2O: 0-8%; WO3: 0-8%; Al2O3: 0-5%; Yb2O3: 0-8%; GeO2: 0-5%; Clarifier: 0-1%;
[0008] Among them, (Gd2O3+ZnO) / Y2O3 is less than 2.0;
[0009] The RO is one or more of MgO, CaO, SrO and BaO;
[0010] The Rn2O is one or more of Li2O, Na2O, and K2O;
[0011] The clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2;
[0012] The refractive index nd of the optical glass is 1.82 to 1.89, the Abbe number vd is 37 to 44, and the thermal expansion coefficient α -30 / 70℃ 85×10 -7 / K or less, wear degree F A It is 75 to 120.
[0013] Optionally, the content of the components is as follows, by weight percentage:
[0014] SiO2: 4~15.2%; B2O3: 10~20%; La2O3: 43~55%; Y2O3: 5~15%; ZrO2: 2~12%; Nb2O5: 3~13%; Gd2O3: 0~5%; ZnO: 1~8%; Ta2O5: 0~5%; TiO2: 0~4%; RO: 0~5%; Rn2O: 0~4%; WO3: 0~6%; Al2O3: 0~3%; Yb2O3: 0~3%; GeO2: 0~3%; Clarifier: 0~0.5%.
[0015] Optionally, the content of the components is:
[0016] SiO2: 6~12%; B2O3: 12~18%; La2O3: 46~52%; Y2O3: 7~13%; ZrO2: 3~10%; Nb2O5: 5~11%; Gd2O3: 0~2%; ZnO: 2~7%; Ta2O5: 0~2%; TiO2: 0~2%; RO: 0~2%; Rn2O: 0~2%; WO3: 0~4%; Al2O3: 0~1%; Yb2O3: 0~1%; GeO2: 0~1%; Clarifier: 0~0.2%.
[0017] Optionally, the content of each component satisfies at least one of the following conditions:
[0018] La2O3 / (B2O3+Nb2O5) is 1.7 to 2.7;
[0019] (ZnO+Ta2O5) / Nb2O5 is 0.1 to 0.8;
[0020] (ZnO+WO3) / Nb2O5 is 0.2-1.0;
[0021] (B2O3+RO) / La2O3 is 0.2~0.4.
[0022] Optionally, the content of each component satisfies at least one of the following conditions:
[0023] (Gd2O3+Ta2O5+WO3) / La2O3 is less than 0.2;
[0024] (Ta2O5+Gd2O3) / Y2O3 is less than 0.2;
[0025] (Gd2O3+ZnO) / Y2O3 is less than 0.8.
[0026] Optionally, the components of the optical glass do not contain one or a combination of two or more of Ta2O5, Gd2O3, RO, Rn2O, Al2O3, Yb2O3 and GeO2.
[0027] Optionally, the refractive index nd of the optical glass is 1.84 to 1.87, the Abbe number vd is 39 to 42, and λ 70 is less than 390nm, λ5 is less than 340nm, Knoop hardness H K 695×10 7 Pa or above, Young's modulus E is 11500×10 7 Pa or more; the density of the optical glass is 4.80g / cm 3 Below, the thermal expansion coefficient α -30 / 70℃ 70×10 -7 / K or less; the water resistance stability of the optical glass DW CR is above 2, and the acid resistance stability is D A It is above Class 2, the bubble degree is above Class A, and the abrasion degree is F A It is 86 to 105.
[0028] The present application also proposes an optical glass preform, which is made of the above optical glass.
[0029] The present application also proposes an optical element, which is made of the above optical glass, or made of the above optical glass preform.
[0030] The present application also proposes an optical instrument, which contains the above optical glass and / or the above optical element.
[0031] The optical glass of the present application uses SiO2, B2O3, La2O3, Y2O3, ZrO2, Nb2O5, Gd2O3, ZnO, Ta2O5, TiO2, RO, Rn2O, WO3, Al2O3, Yb2O3, GeO2 and clarifier as raw materials. SiO2 has the functions of adjusting optical constants, improving chemical stability of glass, maintaining viscosity suitable for molten glass, reducing abrasiveness and reducing corrosion to refractory materials; B2O3 can improve the fusibility and devitrification resistance of glass, which is beneficial to reducing the transition temperature of glass; La2O3 is an effective component for improving the refractive index of glass, and has a significant effect on improving the chemical stability and devitrification resistance of glass; Y2O3 can improve the refractive index and devitrification resistance of glass, and adjust the Young's modulus of glass; ZrO2 can improve the viscosity, hardness, refractive index and chemical stability of optical glass, and can also reduce the thermal expansion coefficient of glass; Nb2O5 is a high-refractive and high-dispersion component, which can improve The refractive index and devitrification resistance of glass can be improved, and the thermal expansion coefficient of glass can be reduced; Gd2O3 can improve the refractive index and chemical stability of glass; ZnO can adjust the refractive index and dispersion of glass, and reduce the high-temperature viscosity and transition temperature of glass; Ta2O5 has the effect of improving the refractive index and enhancing the devitrification resistance of glass; TiO2 can improve the refractive index of glass; alkaline earth metal oxide RO can adjust the optical constants of glass and optimize the chemical stability of glass, but when its content is high, the devitrification resistance of glass is reduced; alkali metal oxide Rn2O can reduce the transition temperature of glass, adjust the optical constants and high-temperature viscosity of glass, and improve the solubility of glass; WO3 can improve the refractive index and mechanical strength of glass; Al2O3 can improve the chemical stability of glass; Yb2O3 can give glass high refractive and low dispersion properties; GeO2 has the effect of improving the refractive index and devitrification resistance of glass; clarifier can improve the clarification effect of glass and optimize the bubble degree of glass. At the same time, the present application controls the ratio of the total content of Gd2O3 and ZnO to the content of Y2O3 (Gd2O3+ZnO) / Y2O3 to less than 2.0, thereby reducing the thermal expansion coefficient of the glass, optimizing the abrasiveness of the glass, and enabling the glass to obtain a suitable Young's modulus, thereby preventing the hardness of the glass from decreasing. By selecting the above components and rationally designing their contents, the high refractive index optical glass obtained in the present application with a refractive index of 1.82 to 1.89 and an Abbe number of 37 to 44 has a low thermal expansion coefficient and excellent abrasiveness, and can meet the expected requirements. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0033] In view of the technical problems existing in the above-mentioned prior art, an embodiment of the present application provides an optical glass, which comprises the following components by weight percentage:
[0034] SiO2: 2-15.2%; B2O3: 8-22%; La2O3: 40-60%; Y2O3: 3-18%; ZrO2: 1-15%; Nb2O5: 2-15%; Gd2O3: 0-9%; ZnO: 0-10%; Ta2O5: 0-10%; TiO2: 0-6%; RO: 0-10%; Rn2O: 0-8%; WO3: 0-8%; Al2O3: 0-5%; Yb2O3: 0-8%; GeO2: 0-5%; Clarifier: 0-1%;
[0035] Among them, (Gd2O3+ZnO) / Y2O3 is less than 2.0;
[0036] The RO is one or more of MgO, CaO, SrO and BaO;
[0037] The Rn2O is one or more of Li2O, Na2O, and K2O;
[0038] The clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2;
[0039] The refractive index nd of the optical glass is 1.82 to 1.89, the Abbe number vd is 37 to 44, and the thermal expansion coefficient α -30 / 70℃ 85×10 -7 / K or less, wear degree F A It is 75 to 120.
[0040] As an implementation method of the present application, the content of the components is as follows, by weight percentage:
[0041] SiO2: 4~15.2%; B2O3: 10~20%; La2O3: 43~55%; Y2O3: 5~15%; ZrO2: 2~12%; Nb2O5: 3~13%; Gd2O3: 0~5%; ZnO: 1~8%; Ta2O5: 0~5%; TiO2: 0~4%; RO: 0~5%; Rn2O: 0~4%; WO3: 0~6%; Al2O3: 0~3%; Yb2O3: 0~3%; GeO2: 0~3%; Clarifier: 0~0.5%.
[0042] As an implementation method of the present application, the content of the components is as follows, by weight percentage:
[0043] SiO2: 6~12%; B2O3: 12~18%; La2O3: 46~52%; Y2O3: 7~13%; ZrO2: 3~10%; Nb2O5: 5~11%; Gd2O3: 0~2%; ZnO: 2~7%; Ta2O5: 0~2%; TiO2: 0~2%; RO: 0~2%; Rn2O: 0~2%; WO3: 0~4%; Al2O3: 0~1%; Yb2O3: 0~1%; GeO2: 0~1%; Clarifier: 0~0.2%.
[0044] As an implementation method of the present application, the content of each component satisfies at least one of the following conditions:
[0045] La2O3 / (B2O3+Nb2O5) is 1.7 to 2.7;
[0046] (ZnO+Ta2O5) / Nb2O5 is 0.1 to 0.8;
[0047] (ZnO+WO3) / Nb2O5 is 0.2-1.0;
[0048] (B2O3+RO) / La2O3 is 0.2~0.4.
[0049] As an implementation method of the present application, the content of each component satisfies at least one of the following conditions:
[0050] (Gd2O3+Ta2O5+WO3) / La2O3 is less than 0.2;
[0051] (Ta2O5+Gd2O3) / Y2O3 is less than 0.2;
[0052] (Gd2O3+ZnO) / Y2O3 is less than 0.8.
[0053] As an implementation method of the present application, the components of the optical glass do not contain one or a combination of two or more of Ta2O5, Gd2O3, RO, Rn2O, Al2O3, Yb2O3 and GeO2.
[0054] Specifically, SiO2 has the functions of adjusting optical constants, improving the chemical stability of glass, maintaining a viscosity suitable for molten glass, reducing abrasion and reducing erosion of refractory materials. In the present application, the above-mentioned effects are obtained by containing more than 2% SiO2. Preferably, the SiO2 content is more than 4%, and more preferably, the SiO2 content is more than 6%. If the SiO2 content is too high, the melting difficulty of the glass increases and the transition temperature increases. Therefore, the upper limit of the SiO2 content in the present application is 15.2%, and the preferred upper limit is 12%.
[0055] B2O3 can improve the solubility and resistance to devitrification of glass, which is beneficial to lowering the transition temperature of glass. The present application obtains the above-mentioned effect by containing more than 8% B2O3, preferably more than 10% B2O3, and more preferably more than 12% B2O3. However, if the B2O3 content is too high, the chemical stability of the glass will deteriorate, especially the water resistance will deteriorate, and the refractive index and light transmittance of the glass will decrease. Therefore, the B2O3 content of the present application is limited to less than 22%, preferably less than 20%, and more preferably less than 18%.
[0056] La2O3 is an effective component for increasing the refractive index of glass, and has a significant effect on improving the chemical stability and resistance to devitrification of glass. If its content is less than 40%, it is difficult to achieve the required optical constants; if its content is higher than 60%, the devitrification tendency of the glass increases and the thermal stability deteriorates. Therefore, the La2O3 content is limited to 40-60%, preferably 43-55%, and more preferably 46-52%.
[0057] Y2O3 can improve the refractive index and devitrification resistance of glass and adjust the Young's modulus of glass. The present application obtains the above-mentioned effects by containing more than 3% Y2O3. However, if its content exceeds 18%, the chemical stability and weather resistance of the glass will deteriorate. Therefore, the Y2O3 content in the present application is limited to 3-18%, preferably 5-15%, and more preferably 7-13%.
[0058] ZrO2 can improve the viscosity, hardness, refractive index and chemical stability of optical glass, and can also reduce the thermal expansion coefficient of glass. However, when the ZrO2 content is too high, the devitrification resistance of the glass decreases, the melting difficulty increases, the melting temperature rises, and inclusions appear inside the glass and the light transmittance decreases. Therefore, the ZrO2 content in this application is limited to 1-15%, preferably 2-12%, and more preferably 3-10%.
[0059] Nb2O5 is a high-refractive and high-dispersion component, which can increase the refractive index and devitrification resistance of glass and reduce the thermal expansion coefficient of glass. In the present application, the above-mentioned effect is obtained by containing more than 2% Nb2O5. Preferably, the lower limit of the Nb2O5 content is 3%, and the more preferred lower limit is 5%. If the Nb2O5 content exceeds 15%, the thermal stability and weather resistance of the glass will be reduced, and the light transmittance will decrease. Therefore, in the present application, the upper limit of the Nb2O5 content is 15%, preferably 13%, and the more preferred upper limit is 11%.
[0060] Gd2O3 can improve the refractive index and chemical stability of glass, but if its content is higher than 9%, the devitrification resistance and abrasion resistance of glass will deteriorate. Therefore, the content of Gd2O3 is limited to 0-9%, preferably 0-5%, and more preferably 0-2%. In some embodiments, it is further preferred that Gd2O3 is not contained.
[0061] ZnO can adjust the refractive index and dispersion of glass, reduce the high-temperature viscosity and transition temperature of glass. If the ZnO content is too high, the difficulty of glass molding increases and the anti-crystallization performance deteriorates. Therefore, the ZnO content in this application is limited to 0-10%, preferably 1-8%, and more preferably 2-7%.
[0062] Ta2O5 has the effect of increasing the refractive index and improving the devitrification resistance of glass, but if its content is too high, the thermal stability of the glass will decrease, the density will increase, and the optical constants will be difficult to control within the desired range; on the other hand, compared with other components, Ta2O5 is very expensive. From the perspective of practicality and cost, its usage should be minimized. Therefore, the content of Ta2O5 in this application is limited to 0-10%, preferably 0-5%, more preferably 0-2%, and it is further preferred that Ta2O5 is not contained.
[0063] TiO2 can increase the refractive index of glass, but too high a content will greatly reduce the dispersion coefficient and increase the tendency of crystallization, and may even cause the glass to be significantly colored. Therefore, the TiO2 content is limited to 0-6%, preferably 0-4%, and more preferably 0-2%.
[0064] Alkaline earth metal oxide RO can adjust the optical constants of glass and optimize the chemical stability of glass, but when its content is high, the devitrification resistance of glass decreases. Therefore, the RO content is limited to 0-10%, preferably 0-5%, and more preferably 0-2%. In some embodiments, it is further preferred that RO is not contained.
[0065] The alkali metal oxide Rn2O can reduce the transition temperature of glass, adjust the optical constants and high temperature viscosity of glass, and improve the melting property of glass. However, when the content of Rn2O is high, the devitrification resistance and chemical stability of glass are reduced. Therefore, the content of Rn2O in the present application is limited to 0 to 8%, preferably 0 to 4%, and more preferably 0 to 2%. In some embodiments, it is further preferred that Rn2O is not contained.
[0066] WO3 can improve the refractive index and mechanical strength of glass. If the WO3 content exceeds 8%, the thermal stability of the glass decreases and the resistance to devitrification decreases. Therefore, the WO3 content is 0-8%, preferably 0-6%, and more preferably 0-4%.
[0067] Al2O3 can improve the chemical stability of glass, but when its content exceeds 5%, the meltability and light transmittance of glass deteriorate. Therefore, the content of Al2O3 in this application is 0 to 5%, preferably 0 to 3%, and more preferably 0 to 1%. In some embodiments, it is further preferred that Al2O3 is not contained.
[0068] Yb2O3 is also a component that gives glass high refractive index and low dispersion properties. If its content exceeds 8%, the anti-crystallization performance of the glass decreases. Therefore, the content of Yb2O3 is 0-8%, preferably 0-3%, more preferably 0-1%, and further preferably contains no Yb2O3.
[0069] GeO2 has the function of increasing the refractive index and resistance to devitrification of glass, but if its content is too high, the chemical stability of the glass will decrease. On the other hand, compared with other components, GeO2 is very expensive. From the perspective of practicality and cost, its usage should be minimized. Therefore, the content of GeO2 in this application is limited to 0-5%, preferably 0-3%, more preferably 0-1%, and further preferably contains no GeO2.
[0070] In some embodiments, by controlling the ratio of the total content of Gd2O3 and ZnO Gd2O3+ZnO to the content of Y2O3 (Gd2O3+ZnO) / Y2O3 to be below 2.0, the thermal expansion coefficient of the glass can be reduced and the abrasiveness of the glass can be optimized. Preferably, (Gd2O3+ZnO) / Y2O3 is below 1.5. Further, by controlling (Gd2O3+ZnO) / Y2O3 to be below 1.0, the glass can more easily obtain a suitable Young's modulus and prevent the hardness of the glass from decreasing. It is further preferred that (Gd2O3+ZnO) / Y2O3 is below 0.8.
[0071] In some embodiments, the ratio of the total content of Ta2O5 and Gd2O3 Ta2O5+Gd2O3 to the content of Y2O3 (Ta2O5+Gd2O3) / Y2O3 is controlled to be below 1.0, which is beneficial for the glass to obtain suitable abrasiveness, optimize the density and Young's modulus of the glass, and prevent the chemical stability of the glass from deteriorating. It is more preferred that (Ta2O5+Gd2O3) / Y2O3 is below 0.8, further preferred that (Ta2O5+Gd2O3) / Y2O3 is below 0.5, and further preferred that (Ta2O5+Gd2O3) / Y2O3 is below 0.2.
[0072] In some embodiments, the ratio of La2O3 content to the total content of B2O3 and Nb2O5 B2O3+Nb2O5, La2O3 / (B2O3+Nb2O5), is controlled in the range of 1.2 to 5.0, which can increase the Young's modulus of the glass and the bubble degree of the glass. More preferably, La2O3 / (B2O3+Nb2O5) is 1.3 to 4.0. Furthermore, La2O3 / (B2O3+Nb2O5) is controlled in the range of 1.5 to 3.5, which can further increase the hardness of the glass and reduce the thermal expansion coefficient of the glass. More preferably, La2O3 / (B2O3+Nb2O5) is 1.7 to 2.7.
[0073] In some embodiments, the ratio of the total content of B2O3 and RO B2O3+RO to the content of La2O3 (B2O3+RO) / La2O3 is controlled in the range of 0.15 to 0.7, which can improve the bubble degree and weather resistance of the glass. More preferably, ((B2O3+RO) / La2O3 is 0.15 to 0.6. Furthermore, controlling (B2O3+RO) / La2O3 in the range of 0.18 to 0.5 can further improve the hardness of the glass and optimize the thermal expansion coefficient of the glass. It is further preferred that (B2O3+RO) / La2O3 is 0.2 to 0.4.
[0074] In some embodiments, the ratio of the total content of ZnO and Ta2O5 ZnO+Ta2O5 to the content of Nb2O5 (ZnO+Ta2O5) / Nb2O5) is controlled to be below 2.0, which is beneficial to improving the chemical stability and light transmittance of the glass. More preferably, (ZnO+Ta2O5) / Nb2O5 is below 1.5. Furthermore, controlling (ZnO+Ta2O5) / Nb2O5 to be below 1.0 can further improve the Young's modulus and bubble degree of the glass. It is even more preferred that (ZnO+Ta2O5) / Nb2O5 is 0.1 to 0.8.
[0075] In some embodiments, the ratio of the total content of Gd2O3, Ta2O5, and WO3 (Gd2O3+Ta2O5+WO3) to the content of La2O3 (Gd2O3+Ta2O5+WO3) / La2O3) is controlled to be below 0.5, which can reduce the density of the glass and improve the light transmittance of the glass. More preferably, (Gd2O3+Ta2O5+WO3) / La2O3 is below 0.4. Furthermore, by controlling (Gd2O3+Ta2O5+WO3) / La2O3 to be below 0.3, the abrasiveness and thermal expansion coefficient of the glass can be further optimized. It is further preferred that (Gd2O3+Ta2O5+WO3) / La2O3 is below 0.2.
[0076] In some embodiments, the ratio (ZnO+WO3) / Nb2O5 between the total content of ZnO and WO3 ZnO+WO3 and the content of Nb2O5 is controlled to be below 3.0, which can improve the weather resistance of the glass and reduce the density of the glass. It is more preferred that (ZnO+WO3) / Nb2O5 is below 2.0, and it is further preferred that (ZnO+WO3) / Nb2O5 is below 1.5. Furthermore, by controlling (ZnO+WO3) / Nb2O5 within the range of 0.2 to 1.0, the hardness of the glass can be further optimized. Therefore, it is further preferred that (ZnO+WO3) / Nb2O5 is 0.2 to 1.0.
[0077] In some embodiments, the present application can improve the clarification effect of the glass and the bubble degree of the glass by containing 0-1% of one or more components of Sb2O3, SnO, SnO2, and CeO2 as a clarifier. The content of the clarifier is preferably 0-0.5%, and the content of the clarifier is more preferably 0-0.2%. Since the component types and contents of the optical glass of the present application are reasonably designed and its bubble degree is excellent, it is further preferred in some embodiments that no clarifier is contained. In addition, when the Sb2O3 content exceeds 1%, the glass tends to have reduced clarification performance. At the same time, due to its strong oxidizing effect, it promotes the corrosion of platinum or platinum alloy vessels for melting glass and the deterioration of the molding mold. Therefore, the present application preferably has a Sb2O3 content of 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably no Sb2O3. SnO and SnO2 can also be used as clarifiers, but when their content exceeds 1%, the tendency of glass coloring increases, or when the glass is heated, softened and molded again, Sn will become the starting point of crystal nucleation, resulting in a tendency of devitrification. Therefore, the content of SnO2 in this application is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain SnO2. The content of SnO is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain SnO. The role and content ratio of CeO2 are consistent with SnO2, and its content is preferably 0-1%, more preferably 0-0.5%, further preferably 0-0.2%, and further preferably does not contain CeO2.
[0078] In the specific implementation process, in the optical glass of the present application, the oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo, even if they exist alone or are contained in a small amount after compounding, the glass will be colored and absorb at specific wavelengths in the visible light region, thereby weakening the property of the present application to improve the visible light transmittance effect. Therefore, in particular, optical glass with requirements for transmittance at wavelengths in the visible light region does not contain oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag and Mo.
[0079] In the specific implementation process, the oxides of Th, Cd, Tl, Os, Be and Se have a tendency to be controlled in recent years as harmful chemical substances, and environmental protection measures are necessary not only in the manufacturing process of glass, but also in the processing process and the disposal after productization. Therefore, in the case of paying attention to the impact on the environment, except for the inevitable mixing, it is preferred that they are actually not contained. Thus, the optical glass does not actually contain substances that pollute the environment. Therefore, even if special environmental countermeasures are not taken, the optical glass of the present application can be manufactured, processed and discarded.
[0080] In the specific implementation process, in order to achieve environmental friendliness, the optical glass of the present application preferably does not contain As2O3 and PbO.
[0081] As an implementation method of the present application, the refractive index nd of the optical glass is 1.84 to 1.87, the Abbe number vd is 39 to 42, and λ 70 is less than 390nm, λ5 is less than 340nm, Knoop hardness H K 695×10 7 Pa or above, Young's modulus E is 11500×10 7 Pa or more; the density of the optical glass is 4.80g / cm 3 Below, the thermal expansion coefficient α -30 / 70℃ 70×10 -7 / K or less; the water resistance stability of the optical glass D W CR is above 2, and the acid resistance stability is D A It is above Class 2, the bubble degree is above Class A, and the abrasion degree is F A It is 86 to 105.
[0082] Specifically, the refractive index (nd) and Abbe number (vd) of the optical glass are tested according to the method specified in GB / T 7962.1-2010. In some embodiments, the refractive index nd of the optical glass of the present application is preferably 1.85-1.86, and the Abbe number vd is preferably 40-41.
[0083] The short-wave transmission spectrum characteristics of optical glass are expressed by the coloration (λ 70 and λ5) indicates that λ 70 It refers to the wavelength when the glass transmittance reaches 70%, λ 70 The measurement is to use a glass with a thickness of 10±0.1mm and two opposite planes parallel to each other and optically polished, and measure the spectral transmittance in the wavelength range from 280nm to 700nm and the wavelength at which the transmittance is 70%. The so-called spectral transmittance or transmittance is the wavelength at which the incident intensity I is perpendicular to the above surface of the glass. in Light of intensity I passes through the glass and emerges from a plane out The light of the case through I out / I in The amount expressed by λ also includes the transmittance of the surface reflection loss on the above surface of the glass. The higher the refractive index of the glass, the greater the surface reflection loss. Therefore, in high refractive index glass, λ 70 A small value of means that the glass itself is less colored and has a high light transmittance. 70It is below 390nm and λ5 is below 340nm.
[0084] Knoop hardness of optical glass (H K ) is tested according to the test method specified in GB / T7962.18-2010. In some embodiments, the Knoop hardness H of the optical glass of the present application is K 695×10 7 Pa or above.
[0085] Young's modulus (E) is calculated by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity according to the following formula:
[0086]
[0087] G=V S 2 ρ
[0088] Where: E is Young's modulus, Pa;
[0089] G is the shear modulus, Pa;
[0090] V T is the shear wave velocity, m / s;
[0091] V S is the longitudinal wave velocity, m / s;
[0092] ρ is the glass density, g / cm 3 .
[0093] In some embodiments, the Young's modulus E of the optical glass of the present application is 11500×10 7 Pa or above.
[0094] The density (ρ) of the optical glass is tested according to the method specified in GB / T7962.20-2010. In some embodiments, the density ρ of the optical glass of the present application is 4.80 g / cm 3 the following.
[0095] Thermal expansion coefficient of optical glass (α -30 / 70℃ ) The data of -30 to 70°C are tested according to the method specified in GB / T7962.16-2010. In some embodiments, the thermal expansion coefficient α of the optical glass of the present application is -30 / 70℃ 70×10- 7 / K or less.
[0096] Water resistance stability of optical glass (D W ) (Powder method) Tested according to the method specified in GB / T 17129. In some embodiments, the water resistance stability of the optical glass of the present application is D WTwo or more types are used, preferably one type is used.
[0097] The test method for weather resistance (CR) of optical glass is as follows: place the sample in a test box with a saturated water vapor environment of 90% relative humidity, and alternately cycle every 1 hour at 40-50°C. After 15 cycles, the weather resistance category is divided according to the change in turbidity before and after the sample is placed. The weather resistance classification is shown in Table 1 below:
[0098] Table 1
[0099]
[0100] In some embodiments, the weather resistance (CR) of the optical glass of the present application is Class 2 or above, preferably Class 1.
[0101] Acid resistance stability of optical glass (D A ) (Powder method) is tested according to the method specified in GB / T 17129. In some embodiments, the acid resistance stability of the optical glass of the present application is D A Two or more types are used, preferably one type is used.
[0102] The bubble degree of the optical glass is tested according to the method specified in GB / T7962.8-2010. In some embodiments, the bubble degree of the optical glass of the present application is above grade A, preferably above grade A0, and more preferably above grade A. 00 class.
[0103] Abrasiveness of optical glass (F A ) refers to the value obtained by multiplying the ratio of the wear volume of the sample to the wear volume (volume) of the standard sample (H-K9 glass) under exactly the same conditions by 100, and is expressed by the following formula:
[0104] F A =V / V0×100=(W / ρ) / (W0 / ρ0)×100
[0105] Where: V is the volume wear of the sample being tested;
[0106] V0 is the volume wear of the standard sample;
[0107] W is the mass loss of the sample under test;
[0108] W0 is the mass loss of the standard sample;
[0109] ρ is the density of the sample being tested;
[0110] ρ0 is the standard sample density.
[0111] In some embodiments, the abrasiveness F of the optical glass of the present application is A It is 86 to 105.
[0112] The embodiment of the present application also provides an optical glass preform, which is made of the above-mentioned optical glass.
[0113] Specifically, the optical glass can be used to make a glass preform by means of direct drop molding, grinding, or hot press molding. That is, the molten optical glass can be directly drop molded into a glass precision preform, or the glass preform can be made by mechanical processing such as grinding and grinding, or the glass preform can be made by making a preform for molding from the optical glass, hot press molding the preform, and then grinding the preform to make a glass preform.
[0114] It should be noted that the means for preparing the glass preform are not limited to the above-mentioned means.
[0115] The embodiments of the present application further provide an optical element, which is made of the above optical glass, or made of the above optical glass preform.
[0116] Specifically, the optical glass or glass preform of the present application can be formed into a preform, and the preform can be used to perform re-hot pressing, precision stamping, etc. to make various optical elements. The optical element has the excellent properties of optical glass and can be used as various lenses, prisms and other optical elements with high optical value. For example, it can be used as various lenses such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses with spherical or aspherical lens surfaces.
[0117] The embodiments of the present application also provide an optical instrument, which contains the above-mentioned optical glass and / or contains the above-mentioned optical element.
[0118] Specifically, the optical elements formed by the optical glass of the present application can be used to manufacture optical instruments such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment, and monitoring equipment.
[0119] It should be noted that, in the present application, unless otherwise specified, the content and total content of each component are all expressed in weight percentage (wt%), that is, the content and total content of each component are expressed in weight percentage relative to the total amount of glass material converted into oxide composition. Here, the "composition converted into oxide" means that when oxides, complex salts and hydroxides used as raw materials for the optical glass components of the present application are decomposed and converted into oxides during melting, the total amount of the oxide material is taken as 100%.
[0120] Unless otherwise indicated in specific circumstances, the numerical ranges listed in this application include upper and lower limits, "above" and "below" include endpoint values, and all integers and fractions included in the range, without being limited to the specific values listed when the range is defined. "And / or" referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0121] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the optical glass of the present invention; however, as raw materials and / or equipment for producing optical glass, there will be certain impurities or components that are not intentionally added, which will be contained in a small amount or trace amount in the final optical glass, and this situation is also within the scope of protection of the patent of this invention.
[0122] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.
[0123] Example Optical Glass
[0124] According to the contents of each component shown in Table 2-Table 4, 24 types of optical glasses were prepared using the above-mentioned optical glass preparation method, and the characteristics of each optical glass were measured according to the test method described in this application, and the measurement results are shown in Table 2-Table 4.
[0125] Table 2
[0126]
[0127]
[0128]
[0129] Table 3
[0130]
[0131]
[0132] Table 4
[0133]
[0134]
[0135] As can be seen from Tables 2 to 4, the optical glass prepared in the present application has excellent refractive index and Abbe number, as well as low thermal expansion coefficient and excellent abrasion resistance. -30 / 70℃ Minimum 60×10 -7 / K, wear degree F AIn the range of 85 to 106, it is shown that the present application reduces the thermal expansion coefficient of the optical glass to a large extent and optimizes the abrasiveness through reasonable component content design.
[0136] Example Optical Glass Preform
[0137] The optical glass obtained in Examples 1-24 is used to make glass preforms of various lenses, prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, by means of processing such as grinding, or molding such as re-hot pressing, precision stamping, etc.
[0138] Example Optical Components
[0139] The preforms obtained in the above embodiments are annealed to reduce the internal stress of the glass and fine-tune the refractive index so that the optical properties such as the refractive index reach the desired values.
[0140] Next, each preform is ground and polished to produce various lenses and prisms such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. The surface of the obtained optical element may be coated with an anti-reflection film.
[0141] Embodiment Optical Instrument
[0142] The optical element obtained by the above-mentioned optical element embodiment is optically designed to form an optical component or optical assembly by using one or more optical elements, and can be used in, for example, imaging equipment, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, lithography technology, excimer lasers, wafers, computer chips, and integrated circuits and electronic devices including such circuits and chips.
[0143] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.
Claims
1. An optical glass, characterized in that: By weight percentage, it includes the following components: SiO2: 2~15.2%; B2O3: 8~22%; La2O3: 40~60%; Y2O3: 3~18%; ZrO2: 1~15%; Nb2O5: 2~15%; Gd2O3: 0~9%; ZnO: 0 ~10%; Ta2O5: 0~10%; TiO2: 0~6%; RO: 0~10%; Rn2O: 0~8%; WO3: 0~8%; Al2O3: 0~5%; Yb2O3: 0~8%; GeO2: 0~5%; Clarifying agent: 0-1%; Among them, (Gd2O3+ZnO) / Y2O3 is less than 2.0; The RO is one or more of MgO, CaO, SrO and BaO; The Rn2O is one or more of Li2O, Na2O, and K2O; The clarifier is one or more of Sb2O3, SnO, SnO2, and CeO2; The refractive index nd of the optical glass is 1.82 to 1.89, the Abbe number vd is 37 to 44, and the thermal expansion coefficient α -30 / 70℃ 85×10 -7 / K or less, wear degree F A It is 75 to 120.
2. The optical glass according to claim 1, characterized in that: By weight percentage, the content of the components is: SiO2: 4~15.2%; B2O3: 10~20%; La2O3: 43~55%; Y2O3: 5~15%; ZrO2: 2~12%; Nb2O5: 3~13%; Gd2O3: 0~5%; ZnO: 1~8%; Ta2O5: 0~5%; TiO2: 0-4%; RO: 0~5%; Rn2O: 0~4%; WO3: 0~6%; Al2O3: 0~3%; Yb2O3: 0~3%; GeO2: 0~3%; Clarifier: 0~0.5%.
3. The optical glass according to claim 1, characterized in that: By weight percentage, the content of the components is: SiO2: 6~12%; B2O3: 12~18%; La2O3: 46~52%; Y2O3: 7~13%; ZrO2: 3~10%; Nb2O5: 5~11%; Gd2O3: 0~2%; ZnO: 2~7%; Ta2O5: 0~2%; TiO2: 0~2%; RO: 0~2%; Rn2O: 0~2%; WO3: 0~4%; Al2O3: 0~1%; Yb2O3: 0~1%; GeO2: 0~1%; Clarifier: 0~0.2%.
4. The optical glass according to any one of claims 1 to 3, characterized in that: The content of each component satisfies at least one of the following conditions: La2O3 / (B2O3+Nb2O5) is 1.7 to 2.7; (ZnO+Ta2O5) / Nb2O5 is 0.1 to 0.8; (ZnO+WO3) / Nb2O5 is 0.2-1.0; (B2O3+RO) / La2O3 is 0.2~0.
4.
5. The optical glass according to any one of claims 1 to 3, characterized in that: The content of each component satisfies at least one of the following conditions: (Gd2O3+Ta2O5+WO3) / La2O3 is less than 0.2; (Ta2O5+Gd2O3) / Y2O3 is less than 0.2; (Gd2O3+ZnO) / Y2O3 is less than 0.
8.
6. The optical glass according to any one of claims 1 to 3, characterized in that: The components of the optical glass do not contain one or a combination of two or more of Ta2O5, Gd2O3, RO, Rn2O, Al2O3, Yb2O3 and GeO2.
7. The optical glass according to any one of claims 1 to 6, characterized in that: The refractive index nd of the optical glass is 1.84-1.87, the Abbe number vd is 39-42, and λ 70 is less than 390nm, λ5 is less than 340nm, Knoop hardness H K 695×10 7 Pa or above, Young's modulus E is 11500×10 7 Pa or more; the density of the optical glass is 4.80g / cm 3 Below, the thermal expansion coefficient α -30 / 70℃ 70×10 -7 / K or less; the water resistance stability of the optical glass D W CR is above 2, and the acid resistance stability is D A It is above Class 2, the bubble degree is above Class A, and the abrasion degree is F A It is 86 to 105.
8. An optical glass preform, characterized in that: Made of the optical glass according to any one of claims 1 to 7.
9. An optical element, characterized in that: The optical glass is made of the optical glass described in any one of claims 1 to 7, or the optical glass preform described in claim 8.
10. An optical instrument, characterized in that: The optical glass according to any one of claims 1 to 7 and / or the optical element according to claim 9.
Citation Information
Cited By
Environment-friendly heavy lanthanum flint optical glass, preparation method thereof and optical element
CN120794333A